1997
DOI: 10.3109/08037059709061933
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Tubular Function in Essential Hypertensives on Beta-blocker Therapy with Atenolol

Abstract: Renal plasma flow (RPF) and glomerular filtration rate (GFR) were measured during waterloading and constant infusion of [131I]hippuran and [125I]iothalamate in 24 mild to moderate essential hypertensive patients before and after 3.5 months treatment with atenolol. Clearances of sodium and potassium were measured 2-3 hours post-dosing and renal vascular resistance (RVR) and filtration fraction (FF) were calculated. Measurement of clearance of lithium (CLi) and uric acid (Curic acid) was employed to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…A total of 2187 patients were recruited and 42 patients (1.9%) were excluded due to insufficient information of SUA (9), prescription drug use (25), and missing questionnaire data (8). Thus, 2145 patients (1139 men, 1006 women) were included in the statistic analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 2187 patients were recruited and 42 patients (1.9%) were excluded due to insufficient information of SUA (9), prescription drug use (25), and missing questionnaire data (8). Thus, 2145 patients (1139 men, 1006 women) were included in the statistic analysis.…”
Section: Resultsmentioning
confidence: 99%
“…β-blockers are known to induce peripheral and renal vascular resistance. In a clinical investigation of essential hypertensive subjects, after 5 months treatment with β-blockers a decrease in renal plasma flow was associated with a significant reduction in uric acid clearance [25].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, a natriuretic effect of beta-receptor blockade has been reported in experimental congestive heart failure [6], in spontaneously hypertensive rats [19], and in patients with essential hypertension [20]. However, in other studies, the long-term administration of beta-blockers has been found to decrease renal plasma flow and/or urinary sodium excretion [21,22]. In our normotensive subjects, no significant change in renal hemodynamics was found after 1 week of administration, thereby confirming several previous observations [17,18,20].…”
Section: Discussionmentioning
confidence: 97%
“…It seems that this could be due to diuretic-induced hyperuricemia resulting in renal failure. Nevertheless earlier studies have shown that diuretics and β-blockers may deplete renal blood flow and consequently decrease urate clearance [13,14]. A recent animal study showed, however, that hyperuricemia may directly induce renal dysfunction [15,16], and a clinical cohort observation study demonstrated that high serum uric acid levels are associated with a higher incidence of end-stage renal disease [17].…”
Section: Tablementioning
confidence: 96%